Double‐Shelled TiO2 Hollow Spheres Assembled with TiO2 Nanosheets. Issue 18 (6th March 2017) - Zhang, Chao; Zhou, Yuming; Zhang, Yiwei; Zhao, Shuo; Fang, Jiasheng; Sheng, Xiaoli; Zhang, Tao; Zhang, Hongxing
Abstract: High‐quality double‐shelled TiO2 hollow spheres (DHS‐Ti) assembled with TiO2 nanosheets have been synthesized for the first time through a simple hydrothermal treatment of sSiO2 @TiO2 (TiO2 ‐coated solid SiO2 spheres). The double‐shelled structure shows a high BET surface area up to 417.6 m 2  g −1 . Anatase DHS‐Ti of high crystallinity can be obtained without structural collapse by calcination treatment. The effects of cetyl trimethylammonium bromide (CTAB) concentration, pH, and hydrothermal reaction temperature have also been investigated with a series of contrast experiments. A formation mechanism involving the in situ growth of amorphous TiO2 nanosheets followed by the redeposition of dissolved silica species is proposed. Lastly, the DHS‐Ti forming strategy can be extended as a general strategy to fabricate various morphological hollow nanostructures and double‐shelled Pt nanocatalysts by rationally selecting functional sSiO2 nanoparticles as core materials. This work could open up a new strategy for controllable synthesis of complex hollow structures and other functional materials. Abstract : Spot the ball : Double‐shelled hollow spheres of TiO2 were synthesized by hydrothermal treatment of TiO2 ‐coated solid SiO2 spheres. The spheres are comprised of TiO2 nanosheets and can be converted without structural collapse to anatase spheres by calcination. The synthesis method can be readily adapted to form hollow structures with different shapes and compositions